Melissa (previously published as george) eaudiobook - Gino, Alex (Scholastic Audio Books, 2016)
BE WHO YOU ARE. When people look at Melissa, they think they see a boy named George. But she knows she's not a boy. She knows she's a girl. Melissa thinks she'll have to keep this a secret forever. Then her teacher announces that their class play is going to be Charlotte's Web. Melissa really, really, REALLY wants to play Charlotte. But the teacher says she can't even try out for the part... because she's a boy. With the help of her best friend, Kelly, Melissa comes up with a plan. Not just so she can be Charlotte — but so everyone can know who she is, once and for all.